Affirmative action for access to graduate education in Brazil: a current overview of racial quotas in graduate programs in sociology in Brazil (PerCursos, 2026)
This study analyzes the implementation of racial quotas in Graduate Programs in Sociology in Brazil in 2025. It is a qualitative study supported by quantitative data, adopting a descriptive-analytical approach and documentary research procedures. The corpus consists of public data from CAPES, particularly from the Sucupira Platform, as well as master's and doctoral admission notices for 2025 entry, covering 52 academic programs in the field. The data were collected, systematized, and analyzed through the identification of affirmative action policies contained in the admission notices, classified as exclusive, aggregated, and mixed quotas. For data processing and organization, the Pandas library of the Python programming language was employed, enabling the filtering, systematization, and statistical analysis of the collected data. In dialogue with Munanga ([1990] 2004), Campos (2012), Baniwa (2013), and Carvalho (2022), the results show that 92.31% of the analyzed programs adopt affirmative action policies aimed at expanding access for marginalized groups, including racial quotas. These findings highlight the prominent role of Sociology in the institutionalization of such policies within Brazilian graduate education.
Keywords: affirmative action; racial quotas; graduate studies in sociology; CHSSALL Alterity project